L-theanine relieves acute alcoholic liver injury by regulating the TNF-α/NF-κB signaling pathway in C57BL/6J mice. (November 2021) - Sun, Lingli; Wen, Shuai; Li, Qiuhua; Lai, Xingfei; Chen, Ruohong; Zhang, Zhenbiao; Li, Dongli; Sun, Shili
Graphical abstract: Highlights: The mouse model of AALI was established by one-time excessive drinking. L-theanine alleviate AALI may by regulating the TNF-α/NF-κB signaling pathway. L-theanine also has a protective effect on LO2 cells damage caused by alcohol. The mechanism of L-theanine on AALI may be the same in mice and LO2 cells. Abstract: Acute alcoholic liver injury (AALI) refers to the inflammatory hepatic damage caused by alcohol. In severe cases, it can lead to steatohepatitis, alcoholic fibrosis and even cirrhosis. In this study, we analyzed the hepatoprotective activity of L-theanine on mice fed with a large amount of ethanol at one time, and the underlying molecular mechanism. The extensive liver injury caused by alcohol feeding was alleviated by L-theanine, which reduced tissue damage, decreased transaminase levels, and increased antioxidant activity. Mechanistically, L-theanine downregulated phosphorylated NF-κB, TNF-α and IKKα in the liver tissues and the LO2 normal hepatocyte cell line, which in turn lowered secretion of iNOS, IL-1β and IL-6. Taken together, L-theanine prevents alcohol-induced liver inflammation by blocking the intrahepatic TNF-α/NF-κB pathway, and is a promising treatment strategy against AALI.